Analisis Kompetensi Pedagogik Mahasiswa Magang dalam Pembelajaran Bahasa Inggris di SD Muhammadiyah Ternate - Darastita Umawaitina; Khusnul Khatima Maru; Nur Ribi Kedafota; Natasya Abedi; Jiatri Buamona; Fatma Nasser; Hariyanti Djafar (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the pedagogical competence of an English Education pre-service teacher intern in designing and implementing English instruction at an elementary school. A descriptive qualitative approach with a single case study was employed during a teaching internship at SD Muhammadiyah Kota Ternate from 6 May to 3 June 2026. The results show that the intern was able to design a teaching module for Unit 6 “Parts of Our Body that Work Together”, although it required two rounds of revision before being approved, and successfully implemented vocabulary instruction on body parts using flashcard media, which was shown to increase student participation and comprehension. The main challenges faced were classroom management and understanding diverse student characteristics, which were gradually addressed through reflection mentoring from the cooperating teacher and field supervisor.